O upcycling na construção de novas peças do vestuário a partir de itens em desuso - Moura, Tainara Schuquel de (2017)
The present Work aims to create a collection of fashion products using the concept of Upcycling, which was obtained through the study as an alternative to prolong the useful life of the pieces that are in disuse. The research is characterized as exploratory and comprised the following stages: the bibliographic review to better understand the topic addressed and a research applied through a questionnaire directed to the target audience for the development of the collection.